Forms of Show Kuda Lumping Ronggo Budoyo in The Village of Lematang Jaya, Lahat, South Sumatera - Anggraini, Erna; Cahyono, Agus (Universitas Negeri Semarang, 2018)
Kuda Lumping is a popular Javanese art, Kuda Lumping is also called Jaran Kepang or Jathilan. Kuda Lumping is a traditional Javanese dance showing a group of warriors riding on horses which the horses are made of buffalo leather that has been dried or made from plait work of bamboo which is then given a motif or ornament and designed like a horse. This study aims to analyze how and understand the form of art performances Kuda Lumping in Lematang Jaya Village, Merapi Timur, Lahat. Theoretically, the research uses interdisciplinary ethnocoreology approach, art sociology, art psychology, and aesthetics. The research methodology uses qualitative research by describing and interpreting the findings in the field. The study used case study design. Data collection techniques used interviews, observations and document studies. Data validity technique used is source triangulation while data analyst technique is done by reducing data, presenting data and drawing conclusion. The results showed that Ronggo Budoyo's lumping horse performance was divided into three phases first before the show consisting of preparation of motion and music practice, dancers dance, property and offerings / offerings. Both times the show opens with a small Pegon dance, followed by Blind dance, a teenage Pegon dance, Kucingan and ends with an adult Pegon dance. The last phase is after the show is the activity to restore the awareness of dancers by the handler and cleans up the dance music and dance equipment.